"'That's a damn good officer any day of the week': inmates' perceptions of correctional officers". Issue 2 (3rd April 2018) - Vieraitis, Lynne M.; Medrano, Justine; Shuraydi, Amny
Abstract: Correctional scholars have suggested that research describing the world of imprisonment can help illuminate some of the consequences of incarceration, specifically how individuals experience incarceration and the ways in which these experiences effect their reentry and reintegration into society. The present study examines the perceptions, daily interactions, and relationships between prison inmates and correctional officers from the perspectives of those who have been incarcerated. Qualitative, in-depth interviews of men released from Texas prisons focus on former inmates' personal experiences and perceptions toward correctional officers while serving time.